PENGARUH RETURN ON ASSET (ROA), RETURN ON EQUITY (ROE), DEBT TO EQUITY RATIO (DER), DAN GOOD CORPORATE GOVERNANCE (GCG) TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2016 – 2020 - Faisal Pratama; Rahmi Widyanti; Basuki Basuki (Al-Kalam Jurnal Komunikasi, Manajemen dan Bisnis, 2023)
The purpose of this study is to examine and analyze: (1) The partial effect of Return On Assets (ROA) on Stock Returns in Manufacturing Companies in the Food and Beverage Sub-Sector Listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period, (2) The effect of Partially Return On Equity (ROE) on Stock Returns in Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) for the 2016 – 2020 Period, (3) Partial Effects of Debt To Equity Ratio (DER) on Stock Returns in Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) 2016 – 2020 Period, (4) Partial Effects of Good Corporate Governance (GCG) on Stock Returns in Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) Period 2016 – 2020, and (5) Simultaneous Effects of ROA, ROE, DER, and GCG on Stock Returns in Manufacturing Companies in the Food and Beverage Sub-Sector g Listed on the Indonesia Stock Exchange (IDX) for the 2016 – 2020 period. Data obtained from the results of the company's financial performance questionnaire (ROA) , ROE and DER), stock returns and Good Corporate Governance (GCG) obtained on the website www.idx.co.id. and processed with data analysis techniques using the SPSS for Windows program. Based on the results of data analysis shows that: (1) Partially there is a significant effect of Return on Assets (ROA) on Stock Return of food and beverage companies listed on the Indonesia Stock Exchange (IDX). (2) Partially there is a significant effect of Return On Equity (ROE) on Stock Return of food and beverage companies listed on the Indonesia Stock Exchange (IDX). (3) Partially there is a significant effect of the Debt to Equity Ratio (DER) on the Stock Return of food and beverage companies listed on the Indonesia Stock Exchange (IDX). (4) Partially there is a significant effect of Good Corporate Governance (GCG) on the Stock Return of food and beverage companies listed on the Indonesia Stock Exchange (IDX). (5) Simultaneously there is a significant effect of ROA, ROE, DER and GCG on stock returns of food and beverage companies listed on the Indonesia Stock Exchange (IDX).